IMPLEMENTASI METODE IQRO’ DALAM PEMBELAJARAN MEMBACA AL-QUR’AN - Tsaqifa Taqiyya Ulfah; Muhammad Shaleh Assingkily; Izzatin Kamala (Universitas Islam Sultan Agung, 2019)
The purpose of this research is to describe implement the Iqro’ method which learning to read the Qur’an at TKA-TPA “AMM” Kotagede Yogyakarta, to explain the systematic, and advantage the Iqro’ method. The research uses the type of qualitative research by describing the data that has been collected as research and field research as a place of research. The results of this research are the implementation of the Iqro’ method which learning to read the Qur’an at TKA-TPA “AMM” Kotagede Yogyakarta based on the main principles of classical and private. Other principles such as, directly introduce the sound of hijaiyah, for kindergarten age are allowed to read, CBSA system and teaching have a purpose. Systematic Iqro’ method which learning to read the Qur'an through stage start from volumes 1-6. Iqro’ method is arranged from concrete to abstract, start from easy to difficult, and start from simple to complex. The Iqro’ method has an advantage, that has been applied throughout Indonesia and some ASEAN countries, flexible, the books are easy to obtain and affordable, use the CBSA system, can finish Iqro’ with a short time, practical, systematic, and varied.Keywords: Iqro’ method, Learning to Read the Qur'an